Evaluating financial distress resolution using prior audit opinions* - KENNEDY, DUANE B.; SHAW, WAYNE H. (Contemporary Accounting Research, 1991)
Abstract. Prior studies have examined whether audit opinions have incremental explanatory power over financial statement data in predicting bankruptcy filings. However, recent regulatory pronouncements indicate that the auditor should attempt to predict impending financial distress (going‐concern difficulties), not whether a firm will file for bankruptcy. This study compares the audit opinion to the resolution of a bankruptcy filing to determine whether prior claims of audit failures might be due to the auditor's focus on financial distress resolution rather than the act of filing for bankruptcy. We find that the audit opinion is a significant variable in a model explaining the resolution of a bankruptcy filing. However, the audit opinion did not predict resolution of bankruptcy proceedings with any greater accuracy than did a naive mechanical model. Résumé. Des chercheurs se sont déjà demandé si l'opinion des vérificateurs avait un pouvoir explicatif marginal par rapport aux données des états financiers dans la prédiction des dépôts de bilan. Or, les règlements récemment promulgués prévoient que les vérificateurs doivent tenter de prédire les difficultés financières imminentes (menaces à la permanence de l'entreprise), et non pas les dépôts de bilan. Les auteurs mettent en parallèle l'opinion du vérificateur et l'issue des dépôts de bilan afin de déterminer si les allégations formulées d'inaptitude des vérificateurs peuvent être attribuables à l'intérêt porté par le vérificateur à la résolution des difficultés financières de l'entreprise plutôt qu'à l'acte du dépôt de bilan. Les auteurs concluent que l'opinion du vérificateur est une variable importante dans un modèle explicatif de l'issue des dépôts de bilan, maís qu'elle ne permet pas de prédire l'issue du déroulement de la faillite avec davantage d'exactitude qu'un modèle mécanique simple.